Deciphering Donald Trump with Mannheim (via Hayden White) and Bobbio: A Peculiar Ideological Interpretation - Gherasim, Gabriel C. (AMERICANA E-journal of American Studies in Hungary, 2021)
The present paper purports to investigate how the views, actions and behaviors of one of the most extraordinary presidential figures of contemporary politics, Donald Trump, could stand the test of an ideological interpretation. To this end, I aim to decipher the baffling, controversial and essentially erratic ideological positioning of the former US president by instrumentalizing two suggestive theoretical undertakings of the concept of political ideology. The first rejuvenates Karl Mannheim’s understanding of the concept of ideology, via its more contextually appropriate and historically accurate reading in Hayden White’s stand-out work Metahistory. The second puts into use Norberto Bobbio’s concept of the "included middle" on Mannheim’s – via White – ideological axis. Accordingly, in line with the present approach, a peculiar ideological interpretation explains Donald Trump’s mostly idiosyncratic stances during the two presidential campaigns and his administration, following three tracks of understanding Trump’s included-middle ideological forays.